The Impact of Safety Factors on Safety Performance (Study on Hydroelectric Power Plants in Sumatra) - Sarah Freshima; Putu Artama Wiguna (Journal of Civil Engineering, 2026)
This research is motivated by the urgency of improving occupational safety in dam maintenance activities at Hydroelectric Power Plants, particularly in the Sumatra region. Although not included in the category of new construction projects, dam structural maintenance and repair activities still contain high risks, especially the potential for technical failures such as seepage which globally is the main cause of dam collapse. At the national level, hydroelectric power plants play a vital role in supporting energy security, but the implementation of Occupational Safety and Health programs is still not optimal. This is reflected in the absence of hydroelectric power plants in Sumatra that have received the Zero Accident award, as well as the number of recurring occupational accidents at several hydroelectric power plants, such as at plants X and Y, over the past five years. This situation emphasizes the need for an in-depth study of the factors that influence the effectiveness of occupational safety systems in the hydroelectric power plant maintenance project sector. This study aims to analyze the influence of safety leadership, safety climate, safety culture, and safety behavior on safety performance, using a quantitative approach with the Partial Least Squares Structural Equation Modeling (SEM-PLS) method. A total of 117 respondents were selected using purposive cluster sampling. The analysis shows that safety culture has the strongest positive influence on safety performance. This research confirms that optimal safety performance can only be achieved through the synergy between a strong safety culture, ingrained safety behaviors, supportive leadership, and a safety climate.